From marginal to essential: the golden thread between nutrient sensing, medium composition and Plasmodium vivax maturation in in vitro culture - Thomson-Luque, Richard; Adams, John H.; Kocken, Clemens H. M.; Pasini, Erica M. (Malaria journal)
Historically neglected, due to its biological peculiarities, the absence of a continuous long-term in vitro blood stage culture system and a propensity towards high morbidity rather than mortality, Plasmodium vivax was put back on the agenda during the last decade by the paradigm shift in the fight against malaria from malaria control to malaria eradication. While the incidence of the deadliest form of malaria, Plasmodium falciparum malaria, has declined since this paradigm shift took hold, the prospects of eradication are now threatened by the increase in the incidence of other human malaria parasite species. Plasmodium vivax is geographically the most widely distributed human malaria parasite, characterized by millions of clinical cases every year and responsible for a massive economic burden. The urgent need to tackle the unique biological challenges posed by this parasite led to renewed efforts aimed at establishing a continuous, long-term in vitro P. vivax blood stage culture. Based on recent discoveries on the role of nutrient sensing in Plasmodium’s pathophysiology, this review article critically assesses the extensive body of literature concerning Plasmodium culture conditions with a specific focus on culture media used in attempts to culture different Plasmodium spp. Hereby, the effect of specific media components on the parasite’s in vitro fitness and the maturation of the parasite’s host cell, the reticulocyte, is analysed. Challenging the wide-held belief that it is sufficient to find the right parasite isolate and give it the right type of cells to invade for P. vivax to grow in vitro, this review contends that a healthy side-by-side maturation of both the parasite and its host cell, the reticulocyte, is necessary in the adaptation of P. vivax to in vitro growth and argues that culture conditions and the media in particular play an essential role in this maturation process.